Development of LKPD based on project-based learning oriented chemo-entrepreneurship on hydrocarbon material for phase F SMA/MA - Velly, Aglin; Suryani, Okta (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This development research was conducted to develop a teaching material in the form of a project-based learning worksheet (LKPD) based on chemo-entrepreneurship-oriented learning on hydrocarbon material for phase F SMA / MA. The validity and level of practicality will be known. The type of research used is educational design research (EDR) with the Plomp development model which has three stages, namely preliminary research (initial investigation), prototyping phase (prototype formation stage), and assessment phase (assessment/testing). However, the assessment phase was not carried out in this study where the research was carried out until the results of the validity and practicality of the LKPD were obtained. The validity test was conducted by 3 chemistry lecturers at FMPA UNP and 2 chemistry teachers at SMAN 3 Padang using a validity questionnaire sheet. Practicality was conducted by 2 chemistry teachers and 9 students of phase F SMAN 3 Padang. The results of the study based on the validity test showed an average Aiken’V 0.87 with a valid category and based on the practicality test showed an average of 90% by students with a very practical category and 94% by teachers with a very practical category. The research results of project-based learning-based LKPD oriented chemo-entrepreneurship on hydrocarbon material for phase F SMA / MA have been valid and practical.